Secondary School in Colombia. Keys to a History of the educational system - Durán Sánchez, María Fernanda (Historia y Memoria de la Educación, 2024)
This article proposes an overview of the historical process —characterized by fragmentation and heterogeneity— of construction of the intermediate level for the Colombian educational system between the end of the 18th century and the first half of the 20th century. In our country, unlike what happens, for example, in the Argentine case, very few works have been interested in offering this panoramic or overall vision of the entire educational system, which can be explained, in part, by the absence of research interested, specifically, in the history of secondary education. As a method of analysis, the scheme is used that is based on the concepts of systematization and segmentation and is organized from the identification of four signs or functions (the propaedeutic, the cultural, the social and the political and economic) in the configuration of the institutional model of secondary education, proposed by Felicitas Acosta for the study of education in Argentina. In the national case, the determining influence that the classic humanist model supported by the Catholic Church has had, and still has today, and has contributed significantly to the weakening of the constitution of a public secondary education system.